Metallurgical Failure Analysis : Techniques and Case Studies - Balan, Kannadi Palankeezhe, author 649899; ScienceDirect (Online service) 7722 (Amsterdam : Elsevier, 2018)
Metallurgical Failure Analysis: Techniques and Case Studies explores how components fail and what measures should be taken to avoid future failures. The book introduces the subject of failure analysis; covers the fundamentals and methodology of failure analysis, including fracture and fractography of metals and alloys and the tools and techniques used in a failure investigation; examines 37 case studies on high performance engineering components; features experimental results comprised of visual-, fractographic-, or metallographic- examination, hardness measurements and chemical analysis; includes illustrations and evidence obtained through test results to enhance understanding; and suggests suitable remedial measures when possible. The various case studies are classified according to the major causes of failures. The case studies pertain to: Improper Material Selection, Manufacturing Defects, Casting Defects, Overload, Fatigue, Corrosion Induced Failures, Hydrogen Embrittlement and Stress Corrosion Cracking, Wear and Elevated Temperature Failures. The book contains information gathered over three decades of the author’s experience handling a variety of failure cases and will go a long way toward inspiring practicing failure analysts. The book is designed for scientists, metallurgists, engineers, quality control inspectors, professors and students alike.